(untitled) (Bangladesh Journal of Microbiology, 2020)
This research was carried out to isolate and identify thermotolerant lactobacilli from broiler chicken gastrointestinal tract from Dhaka, Bangladesh. Twenty five thermotolerant Lactobacillus strains were isolated and identified as Lactobacillus species based on cultural characteristics, biochemical tests, and sugar fermentation. The probiotic are a live microbial feed supplements which positively affects the health of the host animal by improving its intestinal balance.The results showed only four among twenty five isolates were highly responded to probiotic criteria such as low pH tolerance (2.5), bile salt tolerance (2%) and sodium chloride salt tolerance (5%) in vitro, and were identified strains as Lactobacillus plantarum img-02, Lactobacillus plantarum img-08, Lactobacillus plantarum img-10 and Lactobacillus acidophilus img-14 according to Bergey’s Manual of Systematic Bacteriology. Four isolates grow enough at 45°C and two isolates (Lactobacillus plantarum img-10 and Lactobacillus acidophilus img-14) heat stable at 60°C for 30 min. All the strains were showed protease activity on skim milk agar. These strains were resistance to commercial antibiotic ciprofloxacin, gentamycin, imipenem and penicillin G but sensitive to ampicillin, doxycycline, erythromycin and tetracycline; also have antimicrobial activity against common pathogen such as ATCC of Salmonella enteritidis, Staphylococcus aureus, Listeria monocytogenes, Shigella flexneri, Bacillus cereus, Klebsiella pneumonia, Escherichia coli (environmental isolates), Aspergillus flavus and Candida albicans. This study concludes that these isolates may be used as potential candidate as probiotic poultry feed. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 63-68